Income Per Capita and the Structure of Industrial Exports: An Empirical Study - Blejer, Mario I. (The Review of Economics and Statistics, 1978)
T HIS paper sets out to analyze the empirical relationship between the structure of industrial exports and the level of income per capita across 30 countries. To do so, industrial exports are classified according to (a) the factor intensity of their production functions-for the purpose of providing an indirect test of the factor proportions theory of international trade-and (b) the income elasticity of the demand for various goods-for the purpose of testing part of Linder's (1961) hypothesis. Tariffs, subsidies, differential exchange rates, and other bafriers to trade are of crucial importance in the determination of the actual flows of goods between countries. A single variableincome per capita-therefore cannot by itself explain the structure of trade. However, since per capita income reflects the effects of a variety of economic processes and is usually regarded as an indicator of a country's level of development, I believe it worthwhile to analyse the empirical links between the structure of industrial exports and a country's level of development as measured by its per capita income. The sample of 30 countries with a per capita income above U.S. $500 in 1970 includes all the industrial countries and most of the more advanced developing countries. 1,2 I. The Factor Proportions Theory